Crystalline forms of the compound phosphate and methods of making and uses thereof
Patent Information
- Application Number
- CN202610533044.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-22
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-23
AI Technical Summary
化合物可能以一种或多种晶型存在,但是无法具体预期其存在与特性
由于化合物I结晶性差,引湿性强,稳定性差,不利于制剂生产。因此,为了得到具备可接受的理化性质,包括物理化学稳定性、溶解性、吸湿性和/或粒子大小;可制造性以及配制可行性,需要对化合物I进行全面的研究。申请人对化合物I进行了成盐研究,例如本申请发明人研究了化合物I的磷酸盐、甲磺酸盐、盐酸盐、硫酸盐、马来酸盐及苯磺酸盐。与化合物I的其他盐相比,化合物I的磷酸盐具有优异的性质,例如具有较高溶解度的同时具有良好的稳定性和更低的吸湿性,具有较好的粉体性质,有利于制剂加工和生产。
Smart Images

Figure CN122958385A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of crystal chemistry. Specifically, it relates to phosphates of (R)-N-(3-(1-((2-amino-5-(1-methyl-1H-pyrazol-4-yl)pyridin-3-yl)oxy)ethyl)phenyl)-3-(methylthio)benzamide, their crystal forms, preparation methods, and uses. Background Technology
[0002] (R)-N-(3-(1-((2-amino-5-(1-methyl-1H-pyrazol-4-yl)pyridin-3-yl)oxy)ethyl)phenyl)-3-(methylthio)benzamide, having the structure of formula (I), is referred to herein as compound I: (I) The structure of compound I is disclosed in Example 7 of PCT / CN2019 / 078006, which also discloses a treatment method using compound I.
[0003] In the development of small molecule drugs, drug polymorphism is a common phenomenon in drug research and development and an important factor affecting drug quality. A crystal is a solid formed by the three-dimensional ordered arrangement of compound molecules in a microscopic structure. Polymorphism refers to the phenomenon that a compound exists in multiple crystalline forms. A compound may exist in one or more crystal forms, but its specific existence and properties cannot be predicted. The changes in properties caused by different crystal forms can also improve the final formulation. For example, this change can increase solubility, thereby improving bioavailability, or improve the stability of the active ingredient, or, more surprisingly, increase solubility while exhibiting good stability and lower hygroscopicity. For (R)-N-(3-(1-((2-amino-5-(1-methyl-1H-pyrazol-4-yl)pyridin-3-yl)oxy)ethyl)phenyl)-3-(methylthio)benzamide, further research and improvement on its different crystal forms are necessary. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the defect of (R)-N-(3-(1-((2-amino-5-(1-methyl-1H-pyrazol-4-yl)pyridin-3-yl)oxy)ethyl)phenyl)-3-(methylthio)benzamide lacking a pharmaceutically acceptable crystal form, improve its physicochemical properties, and thus provide a compound as shown in formula (I), the pharmaceutically acceptable salt of which is further in the form of a crystalline solid.
[0005] The medicinal salt is selected from organic and / or inorganic salts, specifically, it can be phosphate, methanesulfonate, hydrochloride, sulfate, maleate, benzenesulfonate, nitrate, salicylate, L-tartrate, fumarate, oxalate, etc.
[0006] The pharmaceutically usable salts of Compound I provided by this invention include, for example, phosphates, methanesulfonates, hydrochlorides, sulfates, maleates, benzenesulfonates, nitrates, salicylates, L-tartrates, fumarates, and oxalates, wherein the molar ratio of organic or inorganic acid to Compound I is preferably 0.5:1 to 2:1.
[0007] The compound I provided by this invention is a pharmaceutically usable salt, such as phosphate, methanesulfonate, hydrochloride, sulfate, maleate, benzenesulfonate, nitrate, salicylate, L-tartrate, fumarate, oxalate, which can be hydrated, anhydrous or solvated.
[0008] This invention provides a solid form of the phosphate of compound I, its preparation method and uses, wherein the solid form can be crystalline or amorphous.
[0009] The applicant has discovered a crystalline solid phosphate of compound I that is physically and chemically stable under a range of storage conditions and can be further processed, for example, converted into other solid forms, such as amorphous forms. More surprisingly, the crystalline solid phosphate of compound I exhibits good stability and lower hygroscopicity while increasing solubility.
[0010] Furthermore, this application has discovered anhydrous, hydrated, and solvate forms of the phosphate of compound I, all of which are physicochemically stable crystalline solids under a range of storage conditions.
[0011] The phosphate crystalline solid of compound I provided by the present invention preferably has a molar ratio of phosphoric acid to compound I of 0.5:1-2:1. For example, the molar ratio of phosphoric acid to compound I can be 0.9:1, 1:1 or 1.2:1.
[0012] This invention provides crystalline forms B, C, D, E, F, G, H, I, or K of the phosphate salt of compound I. Names used herein to characterize specific crystalline forms, such as “crystalline form A”, etc., should not be considered as limiting to any other substance having similar or identical physical and chemical properties, but should be understood as identifiers to be interpreted in accordance with the characteristic information described herein.
[0013] The present invention provides a phosphate phosphate of compound I in crystal form B (hereinafter referred to as "crystal form B").
[0014] Without limitation, crystal form B may exhibit isomorphism, and its structure may contain pores / cavities that can accommodate different solvents of suitable size to form solvates. For example, crystal form B may be an N,N-dimethylacetamide solvate or an N-methylpyrrolidone solvate.
[0015] Non-limitingly, the X-ray powder diffraction pattern of crystal form B has characteristic peaks at any one, two, three, four, five, six, or seven locations within the diffraction angle 2θ values of 4.21°±0.2°, 8.31°±0.2°, 11.64°±0.2°, 12.45°±0.2°, 16.30°±0.2°, 18.18°±0.2°, and 20.85°±0.2°.
[0016] Non-limiting, in one specific embodiment of the invention, crystal form B is an N,N-dimethylacetamide solvate. 1 1H NMR results showed that the molar ratio of N,N-dimethylacetamide to compound I phosphate was 1.5:1, corresponding to a mass loss of 21.6 wt% for N,N-dimethylacetamide.
[0017] Non-limiting, in one specific embodiment of the invention, crystal form B is an N-methylpyrrolidone solvate. 1 HNMR results showed that the molar ratio of N-methylpyrrolidone to compound I phosphate was 1.9:1, corresponding to a mass loss of 29.1 wt% for N-methylpyrrolidone.
[0018] The present invention provides a crystal form C of the phosphate of compound I (hereinafter referred to as "crystal form C").
[0019] Without limitation, crystal form C may exhibit isomorphism, and its structure may contain pores / cavities that can accommodate different solvents of suitable size to form solvates. For example, crystal form C can be a dimethyl sulfoxide solvate or an acetone solvate.
[0020] Non-limitingly, the X-ray powder diffraction pattern of the crystal form C has characteristic peaks at any one, two, three, four, five, six, seven, eight, nine, or ten locations within the diffraction angle 2θ values of 5.01°±0.2°, 8.25°±0.2°, 9.33°±0.2°, 10.03°±0.2°, 16.52°±0.2°, 18.00°±0.2°, 18.7°±0.2°, 19.45°±0.2°, 20.16°±0.2°, and 21.87°±0.2°.
[0021] Non-limiting, in one specific embodiment of the invention, crystal form C is a dimethyl sulfoxide solvate. 1 1H NMR results showed that the molar ratio of dimethyl sulfoxide to compound I phosphate was 0.9:1, corresponding to a mass loss of 13.3 wt% for dimethyl sulfoxide.
[0022] Non-limiting, in one specific embodiment of the invention, crystal form C is an acetone solvate.1 1H NMR results showed that the molar ratio of acetone to compound I phosphate was 0.6:1, corresponding to a mass loss of 7.0 wt% of acetone.
[0023] The present invention provides a crystal form D of the phosphate of compound I (hereinafter referred to as "crystal form D").
[0024] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of crystal form D is essentially as follows: Figure 2 As shown.
[0025] Without limitation, the thermogravimetric analysis / differential scanning calorimetry (DSC) plot of crystal form D is basically as follows: Figure 3 As shown in the figure. The results indicate that there is a 7.2 wt% mass loss when heated to 100 °C, and there are two endothermic peaks at 93.9 °C (peak temperature) and 179.8 °C (initial temperature).
[0026] Without limitation, crystal form D is a hydrate.
[0027] Non-limitingly, the X-ray powder diffraction pattern of the crystal form D has characteristic peaks at any one, two, three, four, five, six, seven, eight, nine, ten, eleven, twelve, or thirteen locations within the range of diffraction angles 2θ values of 5.14°±0.2°, 8.02°±0.2°, 10.24°±0.2°, 13.34°±0.2°, 16.11°±0.2°, 17.16°±0.2°, 18.61°±0.2°, 19.57°±0.2°, 21.63°±0.2°, 22.43°±0.2°, 23.41°±0.2°, 24.17°±0.2°, and 25.52°±0.2°.
[0028] The present invention provides a crystalline form E of the phosphate of compound I (hereinafter referred to as "crystalline form E").
[0029] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of crystal form E is essentially as follows: Figure 4 As shown.
[0030] Without limitation, the thermogravimetric analysis / differential scanning calorimetry (DSC) plot of crystal form E is basically as follows: Figure 5 As shown, the weight loss is 1.9 wt% when heated from room temperature to 130 °C, and there are three endothermic peaks at 107.1 °C, 150.7 °C and 180.4 °C (peak temperature).
[0031] Non-limiting, crystal form E is a hydrate.
[0032] Non-limitingly, the X-ray powder diffraction pattern of the crystal form E is as follows: at diffraction angles 2θ of 5.72°±0.2°, 7.98°±0.2°, 8.47°±0.2°, 11.39°±0.2°, 15.21°±0.2°, 16.37°±0.2°, 16.87°±0.2°, 18.11°±0.2°, 19.00°±0.2°, 19.69°±0.2°, and 21... Characteristic peaks are present at any 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16 locations within the range of 0.45°±0.2°, 23.26°±0.2°, 23.58°±0.2°, 24.15°±0.2°, 26.76°±0.2°, and 28.37°±0.2°.
[0033] The present invention provides a crystalline form F of the phosphate of compound I (hereinafter referred to as "crystalline form F").
[0034] Without limitation, crystal form F may exhibit isomorphism, and its structure may contain pores / cavities that can accommodate different solvents of suitable size to form solvates. For example, crystal form F can be a 1,4-dioxane solvate, acetone solvate, acetonitrile solvate, methanol solvate, or tetrahydrofuran solvate.
[0035] Non-limitingly, the X-ray powder diffraction pattern of the crystal form F has characteristic peaks at any one, two, three, four, five, six, seven, eight, nine, ten, or eleven locations within the diffraction angle 2θ values of 5.31°±0.2°, 7.98°±0.2°, 10.56°±0.2°, 13.72°±0.2°, 15.45°±0.2°, 17.81°±0.2°, 18.58°±0.2°, 19.18°±0.2°, 20.14°±0.2°, 20.73°±0.2°, and 22.99°±0.2°.
[0036] Non-limiting, in one specific embodiment of the invention, crystal form F is a 1,4-dioxane solvate, according to... 1 According to the H NMR results, the molar ratio of 1,4-dioxane to compound I phosphate was 0.4:1, corresponding to a mass loss of 6.8 wt% for 1,4-dioxane.
[0037] The present invention provides a crystalline form G of the phosphate of compound I (hereinafter referred to as "crystalline form G").
[0038] Non-limiting, crystal form G 1 1H NMR results indicate that it contains virtually no acetonitrile solvent.
[0039] Non-limitingly, the X-ray powder diffraction pattern of the crystal form G has characteristic peaks at any one, two, three, four, five, six, seven, eight, nine, or ten locations within the diffraction angle 2θ values of 5.59°±0.2°, 7.98°±0.2°, 11.19°±0.2°, 11.88°±0.2°, 14.63°±0.2°, 16.25°±0.2°, 18.08°±0.2°, 21.31°±0.2°, 21.74°±0.2°, and 22.84°±0.2°.
[0040] The present invention provides a crystalline form H of the phosphate of compound I (hereinafter referred to as "crystalline form H").
[0041] Without limitation, crystal form H may exhibit isomorphism, and its structure may contain pores / cavities that can accommodate different solvents of suitable size to form solvates. For example, crystal form H may be an N,N-dimethylacetamide solvate or an N-methylpyrrolidone solvate.
[0042] Non-limiting, in one specific embodiment of the invention, crystal form H is an N,N-dimethylacetamide solvate, according to... 1 According to the H NMR results, the molar ratio of N,N-dimethylacetamide to compound I phosphate was 0.6:1, corresponding to a mass loss of 10.8 wt% for N,N-dimethylacetamide.
[0043] Non-limiting, in one specific embodiment of the invention, crystal form H is an N-methylpyrrolidone solvate, according to... 1 According to the H NMR results, the molar ratio of N-methylpyrrolidone to compound I phosphate was 0.5:1, corresponding to a mass loss of 9.5 wt% for N-methylpyrrolidone.
[0044] Non-limitingly, the X-ray powder diffraction pattern of the crystal form H has characteristic peaks at any one, two, three, four, five, six, seven, eight, or nine locations within the diffraction angle 2θ values of 4.90°±0.2°, 9.74°±0.2°, 14.53°±0.2°, 16.58°±0.2°, 17.67°±0.2°, 19.39°±0.2°, 23.30°±0.2°, 24.33°±0.2°, and 25.42°±0.2°.
[0045] The present invention provides a crystalline form I of the phosphate of compound I (hereinafter referred to as "crystalline form I").
[0046] Without limitation, using Cu-kα radiation, the X-ray powder diffraction pattern of crystal form I is essentially as follows: Figure 17 As shown.
[0047] Non-limitingly, the X-ray powder diffraction pattern of crystal form I has characteristic peaks at any one, two, three, four, five, or six locations at diffraction angles of 4.35°±0.2°, 4.97°±0.2°, 8.68°±0.2°, 9.94°±0.2°, 13.02°±0.2°, and 21.76°±0.2°.
[0048] The present invention provides a crystal form K (hereinafter referred to as "crystal form K") of the phosphate of compound I.
[0049] Non-limiting, the X-ray diffraction structure analysis diagram of crystal form K single crystal is as follows: Figure 19 As shown.
[0050] Without limitation, the unit cell parameters of crystal form K are: a=8.06940(10) b=11.34250(10) c=17.4622(2) α=92.4180(10) β=100.1440(10) γ=99.6820(10) Cell volume: 1546.62(3) Crystal system: Triclinic Space group: P1 The present invention provides a pharmaceutical composition comprising a pharmaceutically acceptable salt (including its crystalline form) of a compound of formula (I) and pharmaceutically acceptable excipients.
[0051] The pharmaceutically acceptable salts (including their crystalline forms) of the compounds of formula (I) provided by this invention are used in the preparation of medicaments for the treatment or prevention of diseases mediated by tyrosine kinases.
[0052] Technical effect Compound I exhibits poor crystallinity, high hygroscopicity, and poor stability, which are detrimental to formulation production. Therefore, to obtain compound I with acceptable physicochemical properties, including physicochemical stability, solubility, hygroscopicity, and / or particle size; manufacturability, and formulation feasibility, a comprehensive study of compound I is necessary. The applicant has conducted salt formation studies on compound I; for example, the inventors of this application have studied phosphate, methanesulfonate, hydrochloride, sulfate, maleate, and benzenesulfonate salts of compound I. Compared with other salts of compound I, the phosphate salt of compound I exhibits superior properties, such as high solubility combined with good stability and lower hygroscopicity, resulting in better powder properties, which is beneficial for formulation processing and production.
[0053] The applicant studied various crystal forms of compound I phosphate, and the results showed that crystal forms B, C, F, H, and K all contained a large amount of solvent.
[0054] The crystal form D provided by this invention can maintain high solubility while exhibiting low hygroscopicity and good stability, and its overall effect is difficult to predict. Specifically, crystal forms D and E have the following unexpected technical effects: (1) Crystal form D remained essentially unchanged in chemical purity when stored at 80 ℃ / 1 day, 25 ℃ / 60%RH / 1 week, and 40 ℃ / 75%RH / 1 week. The crystal form did not change after one week at 25 ℃ / 60%RH. This indicates that crystal form D has good stability under long-term conditions. High temperature and humidity conditions caused by seasonal differences, regional climate differences, and environmental factors can affect the storage, transportation, and production of active pharmaceutical ingredients. The better stability of crystal form D under long-term conditions helps to avoid the impact on drug quality due to crystal transformation or purity decrease during storage.
[0055] (2) The moisture absorption weight gain of crystal form D in 0%RH-80%RH is 2.1wt%, indicating that crystal form D has a weak moisture absorption capacity.
[0056] High hygroscopicity can easily cause chemical degradation and crystal form transformation in active pharmaceutical ingredients (APIs), directly affecting their physicochemical stability. Furthermore, high hygroscopicity reduces the flowability of APIs, thus impacting processing techniques. On the other hand, highly hygroscopic drugs require low humidity levels during production and storage, placing higher demands on manufacturing and resulting in significant costs.
[0057] (3) The solubility of crystal form D in water after 24 hours of equilibrium is 2.7 mg / mL. Crystal form D did not change before and after the test, indicating good stability.
[0058] (4) Crystal form D has a uniform particle size distribution. Uniform particle size helps to ensure content uniformity and reduce the variability of in vitro dissolution, while also simplifying the formulation process.
[0059] (5) The solubility of crystal form E in water after 24 hours of equilibrium is 3.8 mg / mL. Crystal form E did not change before and after the test, indicating good stability. Attached Figure Description
[0060] Figure 1 XRPD diagram of compound I Figure 2 XRPD diagram of crystal form D of the present invention Figure 3 TGA / DSC image of crystal form D of this invention Figure 4 XRPD diagram of crystal form E of this invention Figure 5 TGA / DSC image of crystal form E of this invention Figure 6 For the crystal form E of the present invention 1 H NMR image Figure 7 XRPD image of crystal form B of the present invention. Figure 8 For crystal form B of the present invention 1 H NMR image Figure 9 XRPD image of crystal form C of this invention Figure 10 For crystal form C of the present invention 1 H NMR image Figure 11 XRPD image of crystal form F of the present invention Figure 12 For the crystal form F of the present invention 1 H NMR image Figure 13 Comparison of XRPD images of crystal form F before and after heating (top: crystal form F, bottom: crystal form F after heating) Figure 14 XRPD image of crystal form G of this invention Figure 15 XRPD image of crystal form H of the present invention Figure 16 For the crystal form H of the present invention 1 H NMR image Figure 17 XRPD image of crystal form I of the present invention Figure 18 This is an XRPD image of crystal form I of the present invention after volatilization and drying at room temperature, transforming it into crystal form D. Figure 19 This is an analytical diagram of the X-ray diffraction structure of a single crystal of crystal form K according to the present invention. Figure 20 XRPD diagram of crystal form K of this invention Figure 21 Properties of methanesulfonate sample of compound I Figure 22 Properties of the hydrochloride sample of compound I Figure 23 Properties of sulfate samples of compound I Figure 24 Characteristics of maleate sample of compound I Figure 25 Properties of benzenesulfonate sample of compound I Figure 26 PLM diagram of crystal form D Figure 27XRPD comparison graphs before and after solubility test of crystal form D (top: after equilibrium, bottom: before test). Figure 28 The XRPD comparison graphs before and after the solubility test of crystal form E are shown (from top to bottom: after equilibrium, before equilibrium, and crystal form E reference). Detailed Implementation Plan The present invention will be described in detail below with reference to the embodiments, which describe in detail the methods for preparing and using the crystal forms of the present invention. It will be apparent to those skilled in the art that many modifications to both the materials and methods can be made without departing from the scope of the present invention.
[0061] The abbreviations used in this invention are explained as follows: XRPD: X-ray powder diffraction DSC: Differential Scanning Calorimetry TGA: Thermogravimetric Analysis 1 HNMR: Proton NMR spectrum RH: Relative Humidity PLM: Polarizing microscope DVS: Dynamic Moisture Adsorption IC: Ion chromatography HPLC: High Performance Liquid Chromatography 1 H₂S Solution NMR: Proton NMR spectrum XRPD spectra were acquired using a PANalytical X-ray powder diffractometer, and the XRPD parameters are shown in Table 1.
[0062] Table 1 TGA and DSC spectra were obtained using a TA Q500 / Q5000 / Discovery 5500 thermogravimetric analyzer and a TA... Data were collected on a Q200 / 2000 / Discovery 2500 differential scanning calorimeter. Table 2 lists the test parameters.
[0063] Table 2 DVS curves were acquired on the DVS Intrinsic of SMS (Surface Measurement Systems). Relative humidity at 25°C was corrected for the deliquescence points of LiCl, Mg(NO3)2, and KCl. DVS test parameters are listed in Table 3.
[0064] Table 3 PO4 in the experiment 3- The tests were performed using a ThermoFisher ICS-1100 ion chromatograph, and the test conditions are shown in Table 4.
[0065] Table 4 Purity and solubility tests were performed on an Agilent 1260 HPLC. The instrument and test parameters are shown in Table 5.
[0066] Table 5 1 H₂S solution NMR was acquired on a Bruker 400M NMR spectrometer, DMSO- d 6 or CD3OD as a solvent.
[0067] The "room temperature" mentioned is not a specific temperature value, but refers to a temperature range of 10-30 ℃.
[0068] The term "stirring" refers to the use of conventional methods in the art, such as magnetic stirring or mechanical stirring, at a stirring speed of 50-1800 rpm, wherein magnetic stirring is preferably 300-900 rpm and mechanical stirring is preferably 100-300 rpm.
[0069] The "centrifugation" is performed using conventional methods in the art, such as centrifugation or filtration. The "centrifugation" operation is as follows: the sample to be separated is placed in a centrifuge tube and centrifuged at a rate of 10,000 rpm until all the solids settle to the bottom of the centrifuge tube.
[0070] The "drying" is performed using conventional methods in the art, such as vacuum drying, forced-air drying, or natural air drying. The drying temperature can be room temperature or higher, preferably room temperature to about 60°C, or to 50°C, or to 40°C. The drying time can be 2-48 hours, or overnight. Drying is carried out in a fume hood, forced-air oven, or vacuum oven.
[0071] The term "anhydrous substance" refers to a solid substance that does not contain water of crystallization or a solvent for crystallization.
[0072] The term "hydrate" refers to a solid substance containing water of crystallization.
[0073] The term "solvent" refers to a solid substance containing a crystallizing solvent.
[0074] The term "isomorphic" refers to the phenomenon where, during the crystallization of a substance, the positions of certain molecules at their crystal structure locations are partially or completely replaced by other ions or atoms with similar properties in the medium, resulting in a single-phase crystal that is crystallized together without changing the crystal structure and bonding, only causing a slight change in the unit cell parameters. This is manifested by the same or similar XRPD diagrams of the crystal forms.
[0075] The “characteristic peak” refers to a representative diffraction peak used to identify crystals. When using Cu-ka radiation testing, the peak position can typically have an error of ±0.2°.
[0076] In this invention, "crystal" or "crystal form" can be characterized using X-ray powder diffraction (XRPD). XRPD diffraction data of a crystal has a fingerprint-like quality. Those skilled in the art identify different crystal forms based on XRPD diffraction data. They select several representative peaks from the XRPD pattern as characteristic peaks to characterize the crystal, considering peak position, peak intensity, and peak shape. However, those skilled in the art will understand that X-ray powder diffraction patterns are affected by instrument conditions, sample preparation, and sample purity. The peak intensities in X-ray powder diffraction patterns may also vary with experimental conditions. In fact, the peak intensities in X-ray powder diffraction patterns are related to the preferred orientation of the crystal. The diffraction peak intensities shown in this invention are illustrative rather than for absolute comparison. Therefore, when identifying whether crystal forms are identical, peak position matching is paramount.
[0077] Those skilled in the art will understand that the X-ray powder diffraction pattern of the crystal form protected by this invention need not be completely identical to the X-ray powder diffraction pattern in the embodiments referred to herein. Any crystal form with an X-ray powder diffraction pattern having the same or similar characteristic peaks as those in these patterns falls within the scope of this invention. Those skilled in the art can compare the X-ray powder diffraction pattern listed in this invention with an X-ray powder diffraction pattern of an unknown crystal form to verify whether the two sets of patterns reflect the same or different crystal forms.
[0078] In some embodiments, the crystal form B, C, D, E, F, G, H, I, or K of the present invention is pure and substantially free from any other crystal form. In this invention, "substantially free" when referring to a new crystal form means that the crystal form contains less than 20% (by weight) of other crystal forms, particularly less than 10% (by weight) of other crystal forms, more specifically less than 5% (by weight) of other crystal forms, and even more specifically less than 1% (by weight) of other crystal forms.
[0079] In this invention, the term "about" when used to refer to a measurable value, such as mass, time, temperature, etc., means that it can fluctuate within a certain range around a specific value, such as ±10%, ±5%, ±1%, ±0.5%, or ±0.1%. Detailed Implementation
[0080] Example 1: Preparation method of phosphate of compound I Compound I was prepared according to the preparation method of Compound I disclosed in Example 7 of PCT / CN2019 / 078006. Subsequently, the phosphate of Compound I was obtained according to the salt formation method commonly used in the art. For example, the salt formation reaction of Compound I with the corresponding acid was carried out in solution, and the solvent could be selected from alcohol solvents or mixed solvents of alcohol and water.
[0081] Example 2: Preparation method of crystal form B Weigh 15.3 mg of crystal form A into a 20 mL vial, add N,N-dimethylacetamide (1.0 mL) to dissolve it, and then add the antisolvent ethyl acetate (6.0 mL) dropwise to the vial while stirring. Filter to obtain crystal form B.
[0082] The XRPD pattern of crystal form B is basically as follows: Figure 7 As shown in Table 6, the XRPD data is as follows.
[0083] Crystal form B 1 The H NMR results are as follows Figure 8 As shown, the results indicate that the molar ratio of N,N-dimethylacetamide to compound I phosphate is 1.5:1, corresponding to a mass loss of 21.6 wt% for N,N-dimethylacetamide.
[0084] Table 6 Example 3: Preparation method of crystal form C Weigh 15.0 mg of crystal form A into a 3 mL vial, add 0.2 mL of DMSO, dissolve the solid, place the vial into a 20 mL bottle containing 4.0 mL of acetonitrile, let it stand at room temperature for 12 days, and the solid will precipitate. Centrifuge to obtain crystal form C.
[0085] The XRPD diagram of crystal form C is basically as follows: Figure 9 As shown in Table 7, the XRPD data is as follows.
[0086] Crystal form C 1 The H NMR results are as follows Figure 10 As shown, the results indicate that the molar ratio of dimethyl sulfoxide to phosphate of compound I in crystal form C is 0.9:1, corresponding to a mass loss of 13.3 wt% for dimethyl sulfoxide.
[0087] Table 7 Example 4: Preparation method of crystal form D Weigh 50.0 mg of crystal form A into a small bottle, add water (1.0 mL), stir for 2 days, and centrifuge to obtain crystal form D.
[0088] The XRPD plot of crystal form D is basically as follows: Figure 2 As shown in Table 8, the XRPD data is as follows.
[0089] Thermogravimetric analysis / differential scanning calorimetry (DSC) curves of crystal form D are basically as follows: Figure 3 As shown in the figure. The results indicate that there is a 7.2 wt% mass loss when heated to 100 °C, and there are two endothermic peaks at 93.9 °C (peak temperature) and 179.8 °C (initial temperature).
[0090] Without limitation, crystal form D is a hydrate.
[0091] Table 8 Example 5: Preparation method of crystal form E Weigh 20.2 mg of crystal form A into a 20 mL vial, add acetone (10.7 mL), stir at room temperature for 1 day, centrifuge to obtain a solid, and dry at room temperature for 1 day to obtain crystal form E.
[0092] XRPD diagram of crystal form E is shown below Figure 4 As shown in Table 9, the XRPD data is as follows.
[0093] Crystal form E 1 The H NMR results are as follows Figure 6 As shown, the results indicate that there is essentially no solvent residue in crystal form E.
[0094] Thermogravimetric analysis / differential scanning calorimetry (DSC) curves for crystal form E are basically as follows: Figure 5 As shown, the weight loss is 1.9 wt% when heated from room temperature to 130 ℃, and there are three endothermic peaks at 107.1 ℃, 150.7 ℃ and 180.4 ℃ (peak temperature).
[0095] Non-limiting, crystal form E is a hydrate.
[0096] Table 9 Example 6: Preparation method of crystal form F Weigh 14.5 mg of crystal form A into a 3 mL vial, add 0.5 mL of 1,4-dioxane, stir at 50.0 °C for 5 days, and centrifuge to obtain crystal form F.
[0097] XRPD diagram of crystal form F is shown below Figure 11 As shown in Table 10, the XRPD data is as follows.
[0098] Crystal form F 1The H NMR results are as follows Figure 12 As shown, the results indicate that the molar ratio of 1,4-dioxane to phosphate of compound I in crystal form F is 0.4:1, corresponding to a mass loss of 6.8 wt% for 1,4-dioxane.
[0099] XRPD was tested after heating crystal form F to 135 °C and cooling to room temperature. The XRPD image is shown below. Figure 13 As shown in the figure. The results indicate that crystal form F almost completely transforms into an amorphous form upon heating.
[0100] Table 10 Example 7: Preparation method of crystal form G Weigh 15 mg of crystal form A into a 3 mL vial, add 1.0 mL of a methanol / water (1:1, v / v) mixed solvent, heat to 50 °C and stir until the system is clear, then cool to 5 °C at a rate of 0.1 °C / min and filter to obtain crystal form G.
[0101] XRPD diagram of crystal form G is shown below Figure 14 As shown in Table 11, the XRPD data is as follows.
[0102] Table 11 Example 8: Preparation method of crystal form H Crystal form B was heated to 140 °C and then cooled to room temperature to obtain crystal form H.
[0103] XRPD diagram of crystal form H is shown below Figure 15 As shown in Table 12, the XRPD data is as follows.
[0104] Crystal form H 1 The H NMR results are as follows Figure 16 As shown, the results indicate that the molar ratio of N,N-dimethylacetamide to phosphate of compound I in crystal form H is 0.6:1, corresponding to a mass loss of 10.8 wt% for N,N-dimethylacetamide.
[0105] Table 12 Example 9: Preparation method of crystal form I Weigh 20 mg of crystal form A into a 3 mL vial, add 1.0 mL of a mixed solvent of tetrahydrofuran / water (4:1, v / v), stir until the system is clear, filter, transfer the filtrate to a vial containing polymer (PVC, about 2 mg), seal with sealing film at room temperature, poke a few small holes, and place in a fume hood to evaporate naturally to dryness to obtain crystal form I.
[0106] XRPD pattern of crystal form I is shown below Figure 17 As shown in Table 13, the XRPD data is as follows.
[0107] Crystal form I transforms into crystal form D after evaporation and drying at room temperature. The XRPD comparison diagram is shown below. Figure 18 As shown.
[0108] Table 13 Example 10: Method for preparing single crystals of crystal form K Take 1.0 g of phosphate of compound I, add 100 mL of ethanol / water (5:1, v / v) mixed solvent, sonicate to dissolve, and filter. Filter the solvent system into a test tube and allow it to stand for single crystal growth. After two months, a single crystal sample appeared at the bottom of the test tube. Its unit cell structure contained two molecules of phosphate of compound I, one molecule of water, and three molecules of ethanol, as shown below. Figure 19 The structure shown.
[0109] XRPD diagram of crystal form K is shown below Figure 20 As shown in Table 14, the XRPD data is as follows.
[0110] Table 14 Example 11: Preparation method of methanesulfonate of compound I 1.0 g of compound I was added to 10 mL of dichloromethane and stirred until dissolved at room temperature. Methanesulfonic acid (1.3 eq.) was added dropwise and stirred until dissolved at room temperature. The mixture was refluxed for 30 minutes and allowed to stand at room temperature. Layering occurred, and the sample properties were as follows: Figure 21 As shown.
[0111] Example 12: Preparation method of hydrochloride salt of compound I 1.0 g of compound I was added to 10 mL of acetone and stirred until dissolved at room temperature. Hydrochloric acid (1.3 eq.) was added dropwise, and the mixture was refluxed for 30 minutes. The mixture was then cooled to room temperature and stirred for another 20 hours to obtain a viscous substance. The sample properties are as follows: Figure 22 As shown.
[0112] Example 13: Preparation method of sulfate of compound I 1.0 g of compound I was added to 10 mL of acetone and stirred at room temperature until dissolved. Sulfuric acid (1.3 eq.) was added dropwise, and the mixture was refluxed for 30 minutes. After cooling, a viscous substance was obtained. The sample properties are as follows: Figure 23 As shown.
[0113] Example 14: Preparation method of sulfate of compound I 1.0 g of compound I was added to 10 mL of toluene, stirred at room temperature until partially dissolved, sulfuric acid (1.3 eq.) was added dropwise, refluxed for 30 minutes, and cooled to room temperature to obtain a viscous substance.
[0114] Example 15: Preparation of maleate salt of compound I 1.0 g of compound I was added to 10 mL of acetone and stirred at room temperature until dissolved. Maleic acid was added dropwise with stirring to obtain a clear solution. The solution was refluxed for 30 minutes and cooled to room temperature, where it remained clear without yielding a solid. The properties were as follows: Figure 24 As shown.
[0115] Example 16: Preparation method of benzenesulfonate of compound I 1.0 g of compound I was added to 10 mL of toluene, and after stirring at room temperature, it partially dissolved. Benzenesulfonic acid was then added dropwise with stirring, and the mixture was cooled to room temperature to obtain a viscous substance. The sample properties are as follows: Figure 25 As shown.
[0116] Example 17: Comparison of properties of different salt forms of compound I The properties of the phosphate, methanesulfonate, hydrochloride, sulfate, maleate and benzenesulfonate of compound I are compared in Table 15.
[0117] Table 15 Therefore, it can be seen that the phosphate of compound I has better powder properties compared with other salts, which is beneficial to the production of formulations. At the same time, the phosphate of compound I has high solubility while maintaining good stability and low hygroscopicity, making it very suitable for pharmaceutical development.
[0118] Comparison of the crystal form properties of the phosphate of compound I in Example 18 The applicant obtained phosphates with superior properties by studying the formation of salts of compound I with different acids. Furthermore, the applicant systematically studied the properties of various phosphate crystal forms, hoping to find crystal forms with excellent properties suitable for pharmaceutical development. A comparison of the properties of crystal forms B, C, D, E, F, H, and K of the phosphate of compound I is shown in Table 16.
[0119] Table 16 The comparison results show that crystal forms B, C, F, and H contain more organic solvents and are not suitable for pharmaceutical development.
[0120] Example 19 Stability of Crystal Form D The crystal form D sample was placed under conditions of 80 ℃ / 1 day, 25 ℃ / 60%RH / 1 week and 40 ℃ / 75%RH / 1 week, respectively. The changes in its chemical purity and solid crystal form were evaluated by HPLC area purity and XRPD characterization results. The results are shown in Table 17.
[0121] Table 17 The results showed that the purity of crystal form D did not change significantly after being placed at 80 °C for 1 day and at 25 °C / 60%RH and 40 °C / 75%RH for 1 week. At the same time, the crystal form remained unchanged after 25 °C / 60%RH / 1 week.
[0122] Example 20 Hygroscopicity of Crystal Form D Weigh an appropriate amount of crystal form D of the present invention and test its hygroscopicity using a DVS instrument. Cycle it once at 25 °C, 0%RH-95%RH-0%RH, and record the mass change at each humidity level.
[0123] The results showed that when the humidity increased from 0%RH to 80%RH, the moisture-induced weight gain of crystal form D was 2.1wt%.
[0124] Example 21 Solubility of crystal form D At room temperature, crystal form D was magnetically stirred (700 rpm) in pure water for 24 hours to equilibrate, followed by centrifugation to separate the supernatant and the solid layer. The supernatant was filtered through a 0.22 µm filter and its solubility was tested. The separated solid was then tested for crystal form change using XRPD. The results are shown in Table 18, and the XRPD comparison diagram is shown below. Figure 27 As shown.
[0125] Table 18 The results showed that the solubility of crystal form D in water after 24 hours of equilibrium was 2.7 mg / mL, and the crystal form did not change before and after the test.
[0126] Morphology of crystal form D in Example 22 Crystal form D was characterized using polarized light microscopy (PLM), and the results are as follows: Figure 26 As shown in the figure. The results indicate that crystal form D is a rod-shaped crystal with a grain size of approximately 50-100 µm.
[0127] Example 23 Solubility of crystal form E At room temperature, crystal form E was magnetically stirred in pure water for 24 hours to equilibrate, followed by centrifugation to separate the supernatant and the solid layer. The supernatant was filtered through a 0.22 µm filter and its solubility was tested. The separated solid was then tested for crystal form change using XRPD. The results are shown in Table 19, and the XRPD comparison diagram is shown below. Figure 28 As shown.
[0128] Table 19 The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A phosphate of the compound shown in formula (I), (I), in, The molar ratio of phosphoric acid to the compound of formula (I) is 0.5:1 to 1.5:1, characterized by at least one of the following: (i) Using Cu-kα radiation, the X-ray powder diffraction pattern contains three or more 2θ values selected from the following: 5.14°±0.2°、8.02°±0.2°、10.24°±0.2°、13.34°±0.2°、17.16°±0.2°、18.61°±0.2°、19.57°±0.2°、25.52°±0.2°; (ii) The basic X-ray powder diffraction pattern is shown in Figure 2.
2. A phosphate of the compound shown in formula (I), (I), in, The molar ratio of phosphoric acid to the compound of formula (I) is 0.5:1 to 1.5:1, characterized by at least one of the following: (i) Using Cu-kα radiation, the X-ray powder diffraction pattern contains three or more 2θ values selected from the following: 5.72°±0.2°、7.98°±0.2°、8.47°±0.2°、11.39°±0.2°、15.21°±0.2°、16.87°±0.2°、18.11°±0.2°、19.00°±0.2°、21.45°±0.2°; (ii) The basic X-ray powder diffraction pattern is shown in Figure 4.
3. A pharmaceutical composition comprising a phosphate of a compound of formula (I) according to any one of claims 1-2 and a pharmaceutically acceptable excipient.
4. Use of the phosphate of any one of the compounds of formula (I) according to claims 1-2 in the preparation of medicaments for treating or preventing diseases mediated by tyrosine kinases.